Costos de producción de abono humus y su impacto en la rentabilidad - Cajiao Merino, Cecilia Ivonne (2019)
The research was oriented in the study of the costs of production of fertilizer and its impact on profitability in the company Brando Villacrés Andrés Antonio, located in the city of Guayaquil. The objective of the research is to analyze the impact of the production costs used in the company, in order to determine the value of the units produced that impact the profitability of the company Brando Villacrés Andrés Antonio, for this reason it was considered the development of the interviews and the analysis of the accounting information and with the results collected during the investigation, the practical part could be developed, considering as an idea to defend that the control and efficient analysis of the production costs will allow the company know the impact on the profitability of Humus, reaching the conclusion that the company by increasing the control in the processes and elements of the costs will help with the determination of the sale price and accurately measure the levels of profitability, information that contributes in making efficient decisions…..